Proses Kognitif Dalam Desain Pembelajaran Berbasis Masalah - Haris, Abdul (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2022)
This paper aims to examine the theoretical concept of cognitive process involvement in the design of problem-based learning. Students face difficulties in designing learning, including in carrying out their role in managing learning such as the concept of "Independent Learning". Learning as a thinking activity towards the stage of balancing the structure of experience in long-term memory. A comprehensive and structured cognitive process is needed in designing learning. Good learning design can function flexibly and proportionally in supporting the process of developing student potential in a dynamic learning atmosphere. Problem-based learning designs were developed to stimulate independence and active learning and to provide space for conflict or cognitive processes to occur in the inquiry-discovery process cycle on authentic problems as learning problems. The application of problem-based learning can position students' curiosity, so they are motivated in solving problems through the process of recognizing, understanding, and applying knowledge, thinking critically and creatively in real life. Designing problem-based learning can involve a cycle of cognitive processes; apply-analyze-remember-understand, as a cycle that works on learning analysis activities. The next cycle of cognitive processes occurs; synthesize-evaluate, as an improvement effort.